Influence of Differential Thermochemical Treatment of Bolts on Tightening Parameters in a Bolted Joint - Graboń, W.; Mucha, J.; Osetek, M.; Szlachta, J. (Проблемы прочности, 2016)
This article presents the results of the research into the influence of heat treatment, with application of differential parameters and gas atmosphere, on the friction coefficient during the tightening of a bolted joint. The study consisted of several stages – it included metallographic examinations, hardness evaluation and joint tightening tests. This paper presents the research process, the obtained results and the analysis of the impact of thermochemical treatment on functional parameters, such as friction coefficient and torque, during the tightening of a bolted joint.